CLInical Profile and Side Effects of chronic use of oral Amiodarone in cardiology outpatients department (CLIPSE-A Study)- A prospective observational study. (August 2022) - Fatima, Nabeela; Mandava, Kiranmai; Khatoon, Fatima; Badar, Juveria; Begum, Syeda Fatima; Narasimhan, C.; Daljeet, K.; Mohammed, Walli
Abstract: Background: Amiodarone belongs to Class-III anti-arrhythmic drugs. It is one of the most effective anti-arrhythmic drugs used to treat or prevent several types of arrhythmias including atrial fibrillation, atrial flutter, ventricular tachycardia, and wide complex tachycardia, but unfortunately carries a high toxicity profile. Also, side effects of amiodarone involving various organs can be life-threatening. Materials & methods: This was an observational study carried out for six months i.e from April to September. The study included patients who are on amiodarone for greater than or equal to six months. The required data was collected in-person from the case sheets, treatment charts, and by interviewing the patients. The data for 67 patients was documented in suitable data collection form for analysis. Results: From our study data, it was noted that amiodarone was used for 3 different indications-atrial fibrillation, atrial flutter, and ventricular tachycardia. Among 67 patients enrolled, 38 had no side-effects. Side-effects data in the rest grouped basing on the organ system affected: 9 patients had renal effects, 6 patients had ophthalmic effects, 4 patients had endocrine effects, and 5 patients had hepatic effects. Conclusion: From our study, it is concluded that amiodarone is a safe and effective anti-arrhythmic drug at lower doses i.e. 200-1100 mg/week. When treated in lower doses of 1400–2800 mg/week, many side effects have been incident. Although these effects are mild and develop only after prolonged usage of the drug, it should be used judiciously. Highlights: Amiodarone has an unusual spectrum of side effects with a prevalence of 15% in the first year, increasing up to 50% during long-term use. Our study demonstrated amiodarone does not produce significant side-effects when used in doses of 200–1100 mg/week. Few side-effects are observed when amiodarone is used in higher doses of 1200–2800 mg/week. When a side-effect is observed, mere reducing the dose or withdrawal of drug might help. In most of the cases of atrial fibrillation, amiodarone is discontinued or altered in first year of treatment basing on risk/benefit ratio.